Layoff Orders and Occupational Mobility via Unemployment - Oskari Vahamaa (Aboa Centre for Economics (ACE), 2015)
This paper examines how a change in layoff order can affect the decomposition and the size of unemployment in an equilibrium model where workers make optimal occupational reallocation decisions. In a calibrated model, a policy that concentrates involuntary unemployment incidences to inexperienced workers decreases workers' incentives to reallocate, compared to an equilibrium where everyone faces an identical unemployment risk, leading also to a decrease in aggregate unemployment. Moreover, given that the human capital depreciation during unemployment spells is strong, this policy change increases the market output and on average does not harm inexperienced workers.
Keywords: C71; D85; 330; Layoff order; Occupational Mobility; Unemployment